Applying flipgrid-based portfolio to improve Vietnamese EFL high school students’ speaking scores - Hanh, Le Thi Tuyet; Huong, Tran Thi Bich (Penerbit Universiti Kebangsaan Malaysia, 2021)
During the Covid-19 pandemic, the application of electronic teaching tools has emerged as more crucial than ever. This research was aimed at investigating the impacts of Flipgrid-based portfolio on EFL high school students’ speaking scores and their attitude toward the use of this e-portfolio. The study involved 86 EFL high school students in Vietnam, who were divided into control and experimental groups. The data were collected from a pre-test, a post-test, a questionnaire, and interviews. The results showed that Flipgrid-based portfolio significantly improved students’ speaking performances in terms of pronunciation and fluency. Moreover, all the participants in the experimental group expressed a positive attitude toward the use of this online platform despite some mention of shortcomings. On the basis of the findings, a number of pedagogical recommendations are suggested with the hope of pushing the effective use of e-portfolio in English-language teaching and learning in EFL contexts.